Disenchanted garment workers: social and economic crisis of garment workers - Ahmed, Mirza Tausif (BRAC Univeristy, 2017)
This thesis is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Social Sciences in Economics, 2016.